Creating Systems of Information and Data Structure in Non-profit Performing Arts Management - Sather, Olivia D (ProQuest Dissertations & Theses, 2018)
Capturing institutional memory is a challenge that organizations face in data-driven and digital workplaces. In this project, a system was built to capture institutional memory in the workflow of marketing tasks for the Carpenter Performing Arts Center. The project consisted of three phases of capturing institutional memory: phase one, organizing the marketing shared drive for the Carpenter Performing Arts Center intranet; phase two, creating a database for year-over-year marketing information; and phase three, building a dashboard and series of reports using data captured from the shared drive and database. The project was completed using Microsoft Access database tools and Microsoft Excel due to constraints of the project. This report provides a reflection on the decision-making process throughout the project. The result is a system for capturing institutional memory and streamlining workflow processes for greater efficiently in the organization.